Evaluation of the Abbott m2000 RealTime Human Immunodeficiency Virus Type 1 (HIV-1) Assay for HIV Load Monitoring in South Africa Compared to the Roche Cobas AmpliPrep-Cobas Amplicor, Roche Cobas AmpliPrep-Cobas TaqMan HIV-1, and BioMerieux NucliSENS EasyQ HIV-1 Assays - Scott, Lesley E. (American Society for Microbiology (ASM), 2009)
The implementation of antiretroviral therapy demands the need for increased access to viral load (VL) monitoring. Newer real-time VL testing technologies are faster and have larger dynamic ranges and fully automated extraction to benefit higher throughputs in resource-poor environments. The Abbott RealTime human immunodeficiency virus type 1 (HIV-1) assay was evaluated as a new option for testing for HIV-1 subtype C in South Africa, and its performance was compared to the performance of existing assays (the Cobas AmpliPrep-Cobas TaqMan HIV-1, version 1, assay; the AmpliPrep-Cobas Monitor standard HIV-1 assay; and the NucliSENS EasyQ-EasyMag HIV-1 assay) in a high-throughput laboratory. The total precision of the RealTime HIV-1 assay was acceptable over all viral load ranges. This assay compared most favorably with the Cobas AmpliPrep-Cobas TaqMan HIV-1 assay (R(2) = 0.904), with a low standard deviation of difference being detected (0.323 copies/ml). The bias against comparator assays ranged from −0.001 copies/ml to −0.228 copies/ml. Variability in the reporting of VLs for a 20-member subtype panel compared to the variability of other assays was noted with subtypes G and CRF02-AG. The RealTime HIV-1 assay can test 93 samples per day with minimal manual preparation, less staff, and the minimization of contamination through automation. This assay is suitable for HIV-1 subtype C VL quantification in South Africa.